How does the Green Industry Policy Impact a Developing Country? A Case Study of the Electronic Products and Electrical Equipment Manufacturing Sector in Thailand: 10.32526/ennrj/19/2021028 - Noranarttakun, Phurita; Pharino, Chanathip (Environment and Natural Resources Journal, 2021)
Implementation of Green Industry (GI) strategy has long been recommended for industrial sectors to achieve sustainable production. Among various approaches, GI certification as a voluntary scheme has been implemented widely to promote the adoption of environmental-friendly practices for Thai industrial entrepreneurs. This research examined the progress and lessons learnt from existing schemes and identified the challenges of GI implementation and future improvement. The study particularly focused on small and medium-sized enterprises (SMEs) in the electronic products and electrical equipment manufacturing sector. A questionnaire-based survey was used to collect data, and the Mann-Whitney U Test was used to verify significant barriers and drivers among the samples. The results indicated that major common practices of SMEs are widely approved for fulfilling GI criteria, i.e., waste segregation and minimization, and energy saving, so as to comply with environmental law. While other environmental practices, such as greenhouse gas accounting, green labelling, and green supply chain management were limited in adoption. SMEs, both certified with GI and non-certified with GI, expressed the same opinion that all factors including financial, legal, social, personnel, technological and policies were barriers to GI adoption but significantly different from the economic factor. SMEs in both groups revealed the same opinion that incentive, expertise and technology were drivers of GI adoption but differ significantly from the financial support. Incentive-based instruments such as subsidies and voluntary schemes for green product certification are proposed as appropriate measures to encourage SMEs to adopt GI.